The Impact of Online Marketing Planning on Customer Brand Loyalty in Traditional Arts and Crafts Enterprises in China - Liang, Liu; Shuo, Sun (ASEAN Journal of Management & Innovation, 2025)
Against the backdrop of the rapidly evolving internet and information technologies, traditional craft enterprises are progressively fortifying their e-commerce strategies to broaden their sales channels. However, distinct from other industries, online marketing possesses unique characteristics for traditional craft businesses that can significantly influence consumer behavior. This study aims to examine these characteristics and their specific impact on customer brand loyalty, proposing effective strategies to enhance market competitiveness. To achieve these objectives, the paper will provide a comprehensive review of existing research in this domain, both domestically and internationally. Methodologically, it will employ survey data and statistical analysis to meticulously dissect how the online marketing nuances of traditional craft enterprises affect consumer brand loyalty. Additionally, based on the findings, this study will offer thorough and practical insights and recommendations to both scholars and industry practitioners.